1978
DOI: 10.1182/blood.v51.2.325.bloodjournal512325
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the terminal steps of complement lysis of normal and paroxysmal nocturnal hemoglobinuria red cells

Abstract: The number of microscopically visible lesions produced on the membrane for a given degree of lysis on normal cells as on PNH cells. Since complement lesions were not formed until C8 or C9 was incorporated into the complement sequence, the results suggest that increased lysis of red cells in PNH is due at least in part to more efficient penetration of the PNH membrane by the terminal lytic sequence of complement. Furthermore, the efficiency of the terminal lytic sequence in the lysis of PNH cells when complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…But could DAF deficiency explain all the aberrant interactions of complement with PNH erythrocytes? As noted above, compelling evidence indicated that regulation of the MAC was abnormal on PNH erythrocytes (Rouault et al , 1978; Packman et al , 1979; Parker et al , 1985). Thus, if DAF deficiency alone were sufficient to account for the lytic sensitivity of PNH erythrocytes, DAF would have to play a role (direct or indirect) in the regulation of the MAC.…”
Section: Part II the Modern History Of Pnhmentioning
confidence: 94%
See 1 more Smart Citation
“…But could DAF deficiency explain all the aberrant interactions of complement with PNH erythrocytes? As noted above, compelling evidence indicated that regulation of the MAC was abnormal on PNH erythrocytes (Rouault et al , 1978; Packman et al , 1979; Parker et al , 1985). Thus, if DAF deficiency alone were sufficient to account for the lytic sensitivity of PNH erythrocytes, DAF would have to play a role (direct or indirect) in the regulation of the MAC.…”
Section: Part II the Modern History Of Pnhmentioning
confidence: 94%
“…• The greater efficiency of lysis of PNH erythrocytes is due to aberrant regulation of the membrane attack complex (MAC) of complement (Rouault et al , 1978; Packman et al , 1979)…”
Section: Part II the Modern History Of Pnhmentioning
confidence: 99%
“…Τα ερυθρά αιμοσφαίρια των πασχόντων από ΝΠΑ είναι παθολογικά ευαίσθητα στην δράση του ενεργοποιημένου συμπληρώματος μέσω της κλασσικής ή της εναλλακτικής οδού [Yachnin & Ruthenberg 1965]. H διαταραχή αυτή είναι συνέπεια μιας αυξημένης ευαισθησίας των κυττάρων στα τελικά ενεργοποιημένα κλάσματα του συμπληρώματος [Rouault et al 1978] και έχει σαν αποτέλεσμα μια πολύ μεγαλύτερη καθήλωση C3, σε σχέση με τη φυσιολογική, όταν ενεργοποιηθεί το συμπλήρωμα από αντισώματα (κλασσική οδός) ή από οξυνισθέντα ορό (εναλλακτική οδός). Σε αυτές τις καταστάσεις, η καθήλωση των κλασμάτων C1, C4, C2 και του αντισώματος είναι όμοιες με εκείνες των φυσιολογικών κυττάρων, ενώ υπάρχει μεγάλη περίσσεια C3b.…”
Section: 2 2 α α ε ερ ρυ υθ θρ ρά ά α αι ιμ μο οσ σφ φα αί ίρ ρι ια αunclassified
“…Ο πληθυσμός «τύπου Ι» ΝΠΑ κυττάρων αντιδρά φυσιολογικά, ο πληθυσμός τύπου ΙΙΙ «ΝΠΑ» κυττάρων είναι 15-25 φορές πιο ευαίσθητος στη λύση και ο ενδιάμεσος πληθυσμός ΝΠΑ «τύπου ΙΙ» είναι 3-5 φορές πιο ευαίσθητος από τον πληθυσμό ΝΠΑ «τύπου Ι». Η συχνότητα της διακύμανσης του συνδυασμού των κυτταρικών πληθυσμών από τους οποίους εξαρτάται και η κλινική έκφραση της νόσου είναι οι παρακάτω : Ι+ΙΙΙ: 77%, Ι+ΙΙ και Ι+ΙΙ+ΙΙΙ: 9%, ΙΙ+ΙΙΙ: 3%, μόνο ΙΙ: 1% [Rosse 1971, Rouault et al 1978. Εξάλλου τα ΝΠΑ ερυθρά «τύπου ΙΙΙ» είναι τα μόνα ευαίσθητα στη τελική διαδοχή C5b-9 [Najean et al 1966].…”
Section: 2 2 α α ε ερ ρυ υθ θρ ρά ά α αι ιμ μο οσ σφ φα αί ίρ ρι ια αunclassified